2015
DOI: 10.1073/pnas.1419837112
|View full text |Cite|
|
Sign up to set email alerts
|

Functional connectivity arises from a slow rhythmic mechanism

Abstract: The mechanism underlying temporal correlations among blood oxygen level-dependent signals is unclear. We used oxygen polarography to better characterize oxygen fluctuations and their correlation and to gain insight into the driving mechanism. The power spectrum of local oxygen fluctuations is inversely proportional to frequency raised to a power (1/f) raised to the beta, with an additional positive band-limited component centered at 0.06 Hz. In contrast, the power of the correlated oxygen signal is band limite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
61
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(68 citation statements)
references
References 75 publications
(106 reference statements)
7
61
0
Order By: Relevance
“…These findings are consistent with other observations of quasiperiodicity in brain function, all of which fall into the infraslow regime (Chow et al, 2013; Ko et al, 2011; J. M. Li et al, 2015; Nikulin et al, 2014).…”
Section: Neurophysiological Processes That Could Be Considered Noisesupporting
confidence: 93%
See 1 more Smart Citation
“…These findings are consistent with other observations of quasiperiodicity in brain function, all of which fall into the infraslow regime (Chow et al, 2013; Ko et al, 2011; J. M. Li et al, 2015; Nikulin et al, 2014).…”
Section: Neurophysiological Processes That Could Be Considered Noisesupporting
confidence: 93%
“…Evidence of quasiperiodicity in brain function comes from multiple groups (Chow et al, 2013; Grigg and Grady, 2010; Ko et al, 2011; J. M. Li et al, 2015; Nikulin et al, 2014) and shows that quasiperiodic activity persists across a number of states, including sleep, wakefulness, and anesthesia.…”
Section: Neurophysiological Processes That Could Be Considered Noisementioning
confidence: 99%
“…It was suggested that the default mode network maintains stimulus-independent thoughts or mind wandering (Konishi et al, 2015; Raichle et al, 2001; Weissman et al, 2006). It may set the stage for self-projection and scene construction in the constant switching between interoceptive and exteroceptive mind states (Buckner and Carroll, 2007; Li et al, 2015; Mars et al, 2013). Cytoarchitectonically, cluster 2 was here assigned to area PGa and PGp (Bzdok et al, 2013b; Caspers et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Its activities are principally internal and spontaneous rather than being stimulus‐locked [Andrews‐Hanna, ; Andrews‐Hanna et al, ]. Therefore, top‐down or spontaneous cognitive tasks may modulate activities in the DMN; alternatively, previous studies have revealed that the dominant frequency of DMN is 0.06 Hz or between 0.01 and 0.04 Hz [Li et al, ; Wu et al, ], indicating that a greater resonance may be occurred at lower frequency rather than at 0.1 Hz [Rosanova et al, ]. Both functional and frequency‐specific reasons should be tested in future studies.…”
Section: Discussionmentioning
confidence: 99%